Tinjauan Yuridis Terhadap Pidana Pembebasan Bersyarat yang Dijatuhkan pada Tindak Pidana Korupsi - Rizqyta Amalia Putri, Shafira (Proceedings Series on Social Sciences & Humanities, 2024)
This study discusses the juridical review of parole crimes in corruption crimes. Parole is a form of punishment given to prisoners who have shown awareness and seriousness in solving corruption cases. However, the issue that arises is whether the specific conditions of parole granted to corruption convicts are in accordance with the law and do not conflict with the sense of justice of the community. This study found that Law Number 22 of 2022 concerning Corrections has regulated special parole requirements for corruption convicts. However, there are still some problems that arise in the implementation of this requirement, such as unfairness in granting parole and the potential for parole as a way out to escape responsibility for state losses. In this study, juridical analysis was carried out on laws and regulations related to parole, as well as a review of parole cases that have occurred. The results showed that there is a need for improvement in the parole system so as not to cause injustice and not allow corruption convicts to escape responsibility.